Highly Efficient and Industrially Feasible Interdigitated Back‐Contact Perovskite Solar Cells with Front Carrier Transport Layers Selected Using 2D Simulation. Issue 2 (3rd December 2021) - Li, Ping; Lin, Lingyan; Xiong, Hao; Jiang, Linqin; Lien, Shui-Yang; Li, Jiansheng; Sun, Wen-Hsien; Qiu, Yu
Abstract : Interdigitated back‐contact (IBC) perovskite solar cells (PSCs) have great potential for highly efficient and low‐cost solar energy conversion. However, their full potential has not been achieved. In particular, there is no practically available front surface and rear contact design for IBC‐PSCs as for the conventional crystalline silicon IBCs, which propose challenges in realizing high efficiency. Herein, innovative quasi‐interdigitated back‐contact (QIBC) PSC designs that enhance the effective lateral transport of carriers are proposed and therefore a realistic wide pitch for back contacting in the range of hundreds of micrometers is allowed. The novel design features implementing an appropriate conductive and well‐passivated carrier transport layer, referred to as a front‐carrier transport layer (FCTL), on the front surface of the QIBC‐PSC. Technology computer‐aided design optical/device simulations are used to investigate the function of the FCTL in increasing the cell performance and achieve 23.23% of power conversion efficiency (PCE) after FCTL design optimizations for a QIBC‐PSC with a rear contact pitch of 200 μm. Further improvement of the PCE over 25% can be potentially achievable by improving the film and passivation quality. This work opens up a new approach to fabricate realistic highly efficient IBC‐PSCs. Abstract : An innovative quasi‐interdigitated back‐contact (QIBC) perovskite solar cell (PSC) structure featuring a front‐carrier transport layer (FCTL) and a broad back‐contact pitch is reported. The optimized QIBC‐PSC with CuO FCTL demonstrates the best‐modeled efficiency of 23.23%, with over 25% efficiency available.